INACTIVATION OF RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM. WHICH CLASS OF ANTIHYPERTENSIVE MEDICINE PRODUCTS TO PREFER? - S. V. Stolov (Евразийский Кардиологический Журнал)
A comparative analysis of the effectiveness of two classes of drugs – angiotensin converting enzyme inhibitors (ACEI) and angiotensin II type 1 receptor blockers (ARBS II) in the prevention of cardiovascular diseases is presented. The advantage of ACEI over ARB II in reducing total and cardiovascular mortality, myocardial infarction, brain stroke, chronic heart failure, and chronic kidney disease is shown. The reasons for the different effects of inhibitors of the renin-angiotensin-aldosterone system on the course of cardiovascular pathology are explained by the mechanisms of therapeutic effects of ACEI and ARB II. The antihypertensive  effect of ARB II is provided by selective blockade of AT1 receptors for angiotensin II (at II). As a result of the blockade, an additional amount of at II accumulates in the blood, which binds to AT2 receptors, contributes to the appearance of a number of negative phenomena. Stimulation of AT2-receptors (possibly also AT3-, AT4-receptors) unutilized at II leads to apoptosis of the structural elements of the arterial wall, its fibrosis, sclerosis and hypertrophy, inhibition of coronary remodeling with impaired neovascularization of the myocardium, as well as increased proatherogenic and inflammatory processes in the endothelium, possibly in the heart tissue. Stimulation of AT2 receptors also promotes leukocyte-dependent release of matrix metalloproteinase I, which leads to the destruction of extracellular matrix proteins, thereby destabilizing the atherosclerotic plaque,  leading to its rupture, which is a possible reason for increasing the risk of myocardial infarction during treatment with sartans. The cascade of these negative effects may be the main mechanism of IHD destabilization in the appointment of ARB II. Unlike sartans, the therapeutic potential of ACEI is realized through the blockade of at II synthesis, without affecting the work of the receptor apparatus, so the above adverse effects associated with the accumulation of at II do not occur. An important physiological feature of ACEI is their ability to increase the level of bradykinin, which has a positive effect on the vascular wall, reduces their stiffness by increasing prostaglandin synthesis, demonstrates antioxidant and anti-apoptotic effects, leads to a decrease in afterload and stimulation of angiogenesis. It is these mechanisms that underlie the more pronounced cardioprotective effect of ACEI in contrast to ARB II.